(untitled) (Palíndromo, 2025)
This paper reports on an educational experience conducted during an advanced scientific internship involving a school and a museum. The aim was to discuss Lusotropicalism and the invisibility of the Black presence in the arts, seeking to educate on ethnic-racial relations through an arts-in-education approach. The experience involved an elementary school and the Nogueira da Silva Museum, both in Braga, Portugal. Through a study of the notion of Lusotropicalism, education for ethnic-racial relations, and the role of museums in education, the project sought to develop artistic educational experiences, fostering reflection on the Black presence in the arts, through the articulation between school and museum. The activities led students to question the presence of Black people in society and the arts, which, in our view, contributes to reflection on strategies for integrating arts, images, museums, schools, and artists in the education of ethnic-racial relations. The integration of museums, schools, and the arts, therefore, proves a viable path to deconstructing prejudiced relationships with Black people, highlighting their importance in a democratic society capable of overcoming the cultural legacy of colonialism.